Pengaruh Media Diorama Terhadap Hasil Belajar Pembelajaran IPAS Siklus Air Kelas III Gugus XIX Kota Bengkulu - Rahmadhani, Suci; Dalifa; Susanti, Atika (Universitas Bengkulu, 2024)
This research aims to determine the effect of using diorama media on learning outcomes in science and science learning material on the water cycle for class III elementary school cluster XIX in Bengkulu City. This research is a type of quantitative research. The research method used was a quasi-experimental method with the Matching Only Pretest-Posttest Control Group Design research design. The population in this study were class III students at Gugus XIX Elementary School, Bengkulu City. The research sample was taken using the Cluster Random Sampling technique, resulting in class IIIA of SD Negeri 103 Bengkulu City as the experimental class and class IIIA of SD Negeri 69 Bengkulu City as the control class. The instrument used was a written test sheet in the form of 10 multiple choice questions with data collection techniques in the form of Pretest and Posttest. The test was taken twice, namely before and after learning took place in the experimental class and control class. Based on the results of t-test calculations, students' posttest scores, sig. (2- tailed) is worth 0.000 0.05. This shows that there are differences in posttest results between the experimental class and the control class due to the different treatment of the two classes. So, it can be concluded that there is an influence of the use of diorama media on learning outcomes in science and science learning material on the water cycle for class III elementary school cluster XIX in Bengkulu City.